2004
DOI: 10.1145/1015706.1015804
|View full text |Cite
|
Sign up to set email alerts
|

A stereo display prototype with multiple focal distances

Abstract: Typical stereo displays provide incorrect focus cues because the light comes from a single surface. We describe a prototype stereo display comprising two independent fixed-viewpoint volumetric displays.Like autostereoscopic volumetric displays, fixedviewpoint volumetric displays generate near-correct focus cues without tracking eye position, because light comes from sources at the correct focal distances. (In our prototype, from three image planes at different physical distances.) Unlike autostereoscopic volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
176
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(176 citation statements)
references
References 22 publications
0
176
0
Order By: Relevance
“…The conventional S3D displays fail to render correct retinal blur effects and stimulate natural eye accommodation response, which causes several cue conflicts and is considered as one of the key contributing factors to various visual artifacts associated with viewing S3D displays, such as distorted depth perception [3] and visual discomfort [4]. In recent years, several display methods that are potentially capable of resolving the VAC problem have been demonstrated, including holographic displays [5], volumetric displays [6,7], multi-focal plane displays [8][9][10] and light field displays [11][12][13][14][15][16][17][18][19][20]. Among these different methods, the light field display method is considered as one of the most promising 3D display techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional S3D displays fail to render correct retinal blur effects and stimulate natural eye accommodation response, which causes several cue conflicts and is considered as one of the key contributing factors to various visual artifacts associated with viewing S3D displays, such as distorted depth perception [3] and visual discomfort [4]. In recent years, several display methods that are potentially capable of resolving the VAC problem have been demonstrated, including holographic displays [5], volumetric displays [6,7], multi-focal plane displays [8][9][10] and light field displays [11][12][13][14][15][16][17][18][19][20]. Among these different methods, the light field display method is considered as one of the most promising 3D display techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the simulation of multiple depth cues, the main advantage of DFD is that it avoids the fatigue problems of stereo displays [19] and does not require any user-worn glasses. This technique has been used for a prototype compact display [4], and the interaction between DFD and stereo imaging has been explored [20], [21], but always with two or three parallel screens and a single viewing location. One of our contributions is to show that DFD is still effective for arbitrary screen configurations and viewing locations.…”
Section: Related Workmentioning
confidence: 99%
“…Accommodation is not a very strong depth cue, and by itself is not sufficient to bring out DFD depth impression [2]. On the other hand, we also know that it significantly helps depth impression, when accommodation is in sync with convergence and disparity [20]. The simulator version used in this work represents screens as simple semitransparent polygons onto which the projected images are applied using 2D textures calculated on the fly in offscreen buffers.…”
Section: Simulation Of a General Dfd Displaymentioning
confidence: 99%
“…Rolland et al [7] presented a comprehensive investigation to determine the minimum number of focal planes required for a spatial-multiplexed head-mounted display (HMD). They concluded that an image source consisting of a stack of at least 14 planar displays with a total thickness of 22.5 mm is required to accommodate from 0 to 2 D. Akeley et al developed a three focal-plane prototype by dividing a liquid crystal display (LCD) panel into three zones located at different physical distances with three half mirrors [8] . They studied a depth-filtering rendering technique to determine how the image intensity at each pixel should be assigned to the focal planes, thus reducing the number of focal planes [8,12] .…”
mentioning
confidence: 99%
“…They concluded that an image source consisting of a stack of at least 14 planar displays with a total thickness of 22.5 mm is required to accommodate from 0 to 2 D. Akeley et al developed a three focal-plane prototype by dividing a liquid crystal display (LCD) panel into three zones located at different physical distances with three half mirrors [8] . They studied a depth-filtering rendering technique to determine how the image intensity at each pixel should be assigned to the focal planes, thus reducing the number of focal planes [8,12] . MacKenzie et al then carried out experiments with a similar prototype as that of Akeley et al [9] .…”
mentioning
confidence: 99%